Polynomial Congruence - Amroune, Abir (UNIVERSITE MOHAMED BOUDIAF - M’SILA- FACULTE MATHEMATIQUES ET DE L’INFORMATIQUE, 2019)
We have, in this modest work, interested in the study of polynomial congruences. For this reason we have studied the fundamental notions of the elementary theory of numbers in the first place; then we started the resolution of the polynomial congruences. Throughout the work, the theory was always accompanied by practical examples of calculation. We have understand that concerning a polynomial congruence we can always decide if the congruence has a solution or not, where we can calculate the solutions if they exist.
Keywords: Prime number, Modulus, Polynomial Congruence.